THE EFFECT OF THE PARTICIPATION OF SUCCESSFUL ENTREPRENEURS ON ENTREPRENEURIAL INTENT IN APPLIED ENTREPRENEURSHIP EDUCATION, - Ömer Lütfi Antalyalı; Pınar Göktaş (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
An applied entrepreneurship program was designed as theoretical, game-based and mentor supported for 13-week was implemented twice; to assess its effects on students’ perceived behavioral control, entrepreneurial intention, knowledge and skills. The matching pretest-posttest data were used in the analyses. The program was not found to lead to an increase in entrepreneurial intention. However, they were found to bear a strong potential for more sustainable development of these aspects. The program was implemented as a first in terms of its contribution to the local entrepreneurial ecosystem. The aim of the program was to question its own structure; that is, to find out if the participation of entrepreneurs – a costly feature of the program – really does make a difference in fostering entrepreneurial intentions in the participants. Another unique aspect of the study is that the program brought together actors from academic, business and non-profit fields to collaborate.